Effects of the Menu of Loan Contracts on Borrower Behavior - Abraham, Katharine G.; Filiz-Ozbay, Emel; Ozbay, Erkut Y.; Turner, Lesley J. (Management Science, 2022)
We study how the menu of contracts presented to a decision maker—including contracts she may be precluded from choosing—affects her choice of remunerative but risky actions relative to lower paying, less risky alternatives. We do this through a series of laboratory experiments modeled after the loan repayment options offered to U.S. student borrowers, analyzing borrowers’ task (career) choices in settings that vary the menu of available and unavailable loan repayment plans and knowledge of unavailable options. In these experiments, we observe behavior that is inconsistent with predictions from standard economic models in which agents can easily make complex decisions and each alternative in a choice set is evaluated independently of other potential options. Instead, we provide evidence that expanding the menu of choices or making an agent aware of choices that she has been denied can affect how a contract is valued. Our empirical findings are most consistent with behavioral models that allow for anticipated regret over a choice that turns out to be suboptimal ex post or preferences for simplicity and gratitude for being unburdened from having to make a choice. This paper was accepted by Yan Chen, decision analysis.